2009
DOI: 10.1523/jneurosci.1175-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Increased Synthesis of Spermidine as a Result of Upregulation of Arginase I Promotes Axonal Regeneration in Culture andIn Vivo

Abstract: Adult spinal axons do not spontaneously regenerate after injury. However, if the peripheral branch of dorsal root ganglion neurons is lesioned before lesioning the central branch of the same neurons in the dorsal column, these central axons will regenerate and, if cultured, are not inhibited from extending neurites by myelin-associated inhibitors of regeneration such as myelin-associated glycoprotein (MAG). This effect can be mimicked by elevating cAMP and is transcription dependent. The ability of cAMP to ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 25 publications
3
65
0
Order By: Relevance
“…Treatment with polyamines also promotes axon regeneration in the peripheral nerves (Gilad et al, 1996). Another in vivo study reports that spermidine can promote optic nerve regeneration (Deng et al, 2009). After spinal cord injury of rats, M1 macrophages predominate in sites of trauma and exert neurotoxic effects, but the transient M2 macrophage response promotes repair and axonal growth (Kigerl et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with polyamines also promotes axon regeneration in the peripheral nerves (Gilad et al, 1996). Another in vivo study reports that spermidine can promote optic nerve regeneration (Deng et al, 2009). After spinal cord injury of rats, M1 macrophages predominate in sites of trauma and exert neurotoxic effects, but the transient M2 macrophage response promotes repair and axonal growth (Kigerl et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The first is that viral overexpression of p35 would likely not be a viable approach for clinical applications, from both a technical and safety standpoint, and so alternative means of inducing p35 expression would be required. These could include gene-based therapies or, most logically, exogenous administration of spermidine, which has been shown previously to promote axonal regeneration in the optic nerve (Deng et al, 2009). Importantly, spermidine has been shown to cross the blood-brain barrier following cerebral ischemia (Diler et al, 2002), and so it is possible that entry of spermidine into the CNS would be facilitated after traumatic injury.…”
Section: Discussionmentioning
confidence: 99%
“…We have also demonstrated that arginase I expression and polyamine synthesis are required for the ability of cAMP to reverse myelin-mediated inhibition and that treatment with exogenous putrescine overcome inhibition by MAG in vitro . We subsequently showed that putrescine must be converted to spermidine to have this effect and, most importantly, that spermidine can promote regeneration of retinal ganglion cell axons following optic nerve injury (Deng et al, 2009). In this study, we report that the ability of putrescine to overcome inhibition by MAG and myelin arises from spermidine's function as substrate for the hypusine modification of elongation initiation factor 5A (eIF5A).…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations